Presencia de leones marinos (Carnivora, Pinnipedia, Otariidae) en El Salvador - Ibarra Portillo, Ricardo Enrique (Universidad de El Salvador, 2017)
La información sobre la presencia de Otariidos en El Salvador es poco conocida. Existen 16 registros, siete de los cuales corresponden a cuatro especies (Arctocephalus philippii townsendi, A. galapagoensis, Otaria flavescens y Zalophus californianus), provenientes de los Departamentos de Sonsonate, La Paz y La Unión). Los nueve restantes no fueron identificados a nivel de especie, avistados en cinco departamentos (cuatro en Sonsonate, uno en Ahuachapán, uno en La Paz, uno en La Unión, uno en Usulután y uno más en sitio no determinado). La presencia de estos mamíferos marinos ha estado relacionada con los fenómenos de La Niña o El Niño, siendo cuatro registros en eventos débiles (dos en El Niño y dos en La Niña), siete en modalidad moderada (cinco en El Niño y dos en La Niña) y cuatro en modalidad fuerte (dos en El Niño y dos en La Niña). Todos los registros ocurrieron por individuos en varamiento entre 1970 a 2015.Little is known about the occurrence of Otariids in El Salvador. In the country, there are records of specimens belonging to four species (Arctocephalus philippii townsendi, A. galapagoensis, Otaria flavescens and Zalophus californianus). There are 16 records in all, seven of them identified by species, from three departments (two in Sonsonate, two in La Paz, and three in La Unión) and eight records of unidentified species from five departments (four in Sonsonate, one in Ahuachapán, one in La Paz, one in La Unión, one in Usulután and one more without site).The occurrence of this type of marine mammal has been linked to atmospheric phenomena of El Niño or La Niña since four sightings took place during weak forms (two during El Niño and two during La Niña), seven in moderate modes (five during El Niño and two during La Niña) and four in strong modalities (two during El Niño and two during La Niña). All the records occurred from beached individuals within 1970 to 2015.